Pengabdian Kepada Masyarakat Pelatihan Aplikasi Software CAD dan 3D Printer Bagi Siswa SMK Wahid Hasyim Glagah Sebagai Pengembangan Skill Siswa dalam Menghadapi Era Digital - Miftahul Ulum; Didik Sugiono; Novi Indah Riani; Aini Lostari; Yudi Hartono; Umi Kulsum; Supardi (Universitas Binawan, 2025)
Technology's impact on education and the industrial sector is growing, and in this day and age, it is constantly used in a variety of ways to help people carry out their daily tasks and more. One of these is computer-aided design (CAD) technology. Other technologies that have emerged lately and are helping people with their problems include 3D printing technology. Both of these technologies are widely used as tools that utilize design and real-world projects. SMK education must be characterized by a few technologies that will become the foundation of the working world for students; therefore, instruction and learning must be provided as a means of preparing students for the digital age. Our collaborative efforts with SMK Wahid Hasyim Glagah aim to provide education and training related to the use of design and 3D printing technologies. We use public speaking as one of our teaching methods, along with intense visual and practical training conducted at the Universitas Qomaruddin Gresik Laboratory. The expected outcome of this activity is that the students will be able to use the computer-based design application to create drawings and be able to innovate in various design-related fields independently. They will also be able to use a 3D printer as a source of accurate 3D drawings so they can innovate in the field of business.